Islam dan Nyadran di Kendal Sinkronisasi Ajaran Islam dan Adat Lokal: Tinjauan Kritis Terhadap Tradisi Nyadran (Sedekah Laut) di Pantai Sendang Sikucing Kecamatan Rowosari Kabupaten Kendal dalam Perspektif Pendidikan Islam dan Budaya Jawa - Miftachul Richaniah; Muhammad Ahsanul Husna; Nurul Azizah (Educatio, 2026)
This research aims to critically analyze the synchronization process between Islamic theological values ​​and local wisdom in the Nyadran (Sea Almsgiving) tradition on Sendang Sikucing Beach, Kendal Regency. The main problem studied is the tension between the formal-normative theological perspective which is concerned about shirk and the cultural practices of fishing communities which view this ritual as an expression of gratitude. This research uses a qualitative approach with the type of field research. Data was collected through participatory observation, documentation, and in-depth interviews with religious leaders, traditional leaders and fishing communities. Data analysis was carried out through reduction stages, data presentation and drawing conclusions. The research results show that the Nyadran tradition at Sendang Sikucing Beach is a manifestation of intelligent acculturation that uses the "Tut Wuri Hangiseni" preaching strategy, similar to the Walisongo preaching. Synchronization occurs through "Aqidah Filter" and reinterpretation of intentions, where the meaning of offerings is changed from spiritual offerings to symbols of alms and gratitude to Allah SWT. From the perspective of Islamic education, this tradition contains three main pillars: monotheism education through ritual purification, worship education through philanthropy (orphan compensation and kenduri), and ecological moral education (ethics of protecting the sea). Meanwhile, from a Javanese cultural perspective, Nyadran strengthens the philosophy of Memayu Hayuning Bawana and communal harmony. This research concludes that Nyadran in Sendang Sikucing is not a deviant form of syncretism, but rather a "Middle Way" that integrates Islamic and Javanese identities, as well as being a character laboratory for moderate society.